A Systematic Study of the Cryogenic Milling of Chrysotile Asbestos - Valentina Scognamiglio; Dario Di Giuseppe; Magdalena Lassinantti Gualtieri; Laura Tomassetti; Alessandro F. Gualtieri (Applied Sciences, 2021)
For more than 40 years, intensive research has been devoted to shedding light on the mechanisms of asbestos toxicity. Given the key role of fibre length in the mechanisms of asbestos toxicity, much work has been devoted to finding suitable comminution routes to produce fibres in desired size intervals. A promising method is cryogenic milling that, unlike other mechanical size reduction techniques, preserves the crystal–chemical properties of materials. In this study, the effect of cryogenic milling on the physical–chemical properties of commercial Russian chrysotile was studied in order to produce precise size fractions with invariant properties compared to the pristine fibres. In particular, two batches with fibres > 5 µm and < 5 µm were prepared, as this limit sets their potential toxicity. The results are fundamental for future in vitro toxicity testing of this commercial product, widely used in chrysotile-friendly countries but not yet adequately studied. Results show that fibre length can be controlled by milling time under cryogenic conditions without inducing structural defects or amorphization; short fibres (95% L < 5 µm) can be obtained by cryogenic milling for 40 min, while 10 min is enough to yield long chrysotile fibres (90% L > 5 µm).